Taxation of Re-commerce Through Online Platforms: Cross Comparison Between Selected European Countries and Proposal for Improvement - Náñez Alonso, Sergio Luis (2026)
The sale of second-hand products between individuals has grown exponentially with platforms such as Ebay, Wallapop and Vinted, overwhelming a tax system designed for physical markets. The study is based on this reality: ensuring that sellers declare their income while not burdening those who only occasionally sell household items with red tape. The Spanish General Tax Law, personal income tax, VAT, and property transfer tax have been reviewed, as well as the transposition of the Directive 2021/514 or DAC7. In turn, a comparison is made between several European countries: Spain, France, Germany, Portugal, Italy, and Poland. From 2024, DAC7 will require platforms to report to the tax authorities when a user exceeds thirty transactions or 2000 € in a year, providing the Administration with the traceability it lacked, but without standardizing the way in which each country taxes these sales. Spain stands out for maintaining the ITP on movable property, a residual tax that is rarely paid, highlighting a need for tax simplification and European convergence. The conclusions proposed are as follows: first, to set a single threshold to distinguish between occasional sellers and professionals and prevent tax avoidance by exploiting national differences; second, to concentrate taxation on personal income tax and VAT and eliminate ineffective taxes such as the ITP, or at least exempt microtransactions; third, introduce green incentives (reduced VAT rates and tax credits for repair or resale) to bring taxation into line with circular economy objectives; and, finally, strengthen digital cooperation with standardized registers and clear limits on the use and storage of data, so that transparency does not affect citizens’ privacy.